Kontribusi Technology Acceptance Model (TAM) terhadap Technostress pada Guru Sekolah Dasar Negeri di Wilayah Panti Timur - Jihan Zahira Nurista; Zulmi Yusra (Pusat riset dan Inovasi Nasional, 2025)
Education in the modern era requires teachers to develop their competencies in mastering science and technology to be applied in the learning process. One of the challenges faced by teachers in this era of educational digitalization is technostress. Technostress is the stress experienced by individuals as a result of the use of technology,